Interplay of Atomic Interactions in the Intermetallic Semiconductor Be5Pt. (24th September 2019) - Amon, Alfred; Svanidze, Eteri; Ormeci, Alim; König, Marcus; Kasinathan, Deepa; Takegami, Daisuke; Prots, Yurii; Liao, Yen‐Fa; Tsuei, Ku‐Ding; Tjeng, Liu Hao; Leithe‐Jasper, Andreas; Grin, Yuri
Abstract: Semiconducting substances form one of the most important families of functional materials. However, semiconductors containing only metals are very rare. The chemical mechanisms behind their ground‐state properties are only partially understood. Our investigations have rather unexpectedly revealed the semiconducting behaviour (band gap of 190 meV) for the intermetallic compound Be5 Pt formed at a very low valence‐electron count. Quantum‐chemical analysis shows strong charge transfer from Be to Pt and reveals a three‐dimensional entity of vertex‐condensed empty Be4 tetrahedrons with multi‐atomic cluster bonds interpenetrated by the framework of Pt‐filled vertex‐condensed Be4 tetrahedrons with two‐atomic polar Be−Pt bonds. The combination of strong Coulomb interactions with relativistic effects results in a band gap. Abstract : Mut zur Lücke : Be5 Pt repräsentiert den seltenen Fall eines Halbleiters, der nur aus metallischen Elementen gebildet wird. Die Lücke in der Bandstruktur erscheint sowohl aufgrund relativistischer Effekte als auch einer einzigartigen Bindungssituation mit polaren Zweiatom‐ und Mehratom‐Pt‐Be‐Wechselwirkungen.